2017
DOI: 10.5812/ijpbs.9074
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Borna Disease Virus and Chronic Fatigue Syndrome: A Systematic Review and Meta-Analysis

Abstract: Context: Several studies have controversial results regarding the association between Borna disease virus (BDV) and chronic fatigue syndrome (CFS). The present systematic review and meta-analysis investigated the association between CFS and BDV. Evidence Acquisition: The present study was conducted based on the PRISMA guidelines for systematic review and meta-analysis studies. To avoid bias, all procedures of the study were performed by two researchers independently. A comprehensive search was performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Systematic reviews and metaanalyses can provide a complete view of a problem in the community by examining all relevant documentation and provide a clear picture (49)(50)(51). Given the importance of depression during pregnancy, this study aimed to investigate the prevalence of depression among pregnant women in Iran using the meta-analysis method.…”
Section: Objectivesmentioning
confidence: 99%
“…Systematic reviews and metaanalyses can provide a complete view of a problem in the community by examining all relevant documentation and provide a clear picture (49)(50)(51). Given the importance of depression during pregnancy, this study aimed to investigate the prevalence of depression among pregnant women in Iran using the meta-analysis method.…”
Section: Objectivesmentioning
confidence: 99%
“…Evidence of the association between BDV infection and psychiatric disorders was observed in the study by Azami et al By analyzing 35 studies, significant association was confirmed between BDV infection and schizophrenia, and the estimated OR was 2.72 (95%CI: 1.75 -4.20) (25). In another meta-analysis conducted in 2017 on 9 studies, a significant association was observed between BDV infection and chronic fatigue syndrome, and the estimated OR was 10.41 (95%CI: 4.24 -25.55, P < 0.0001) (26). In addition, significant association was noted between BDV infection and depression in a meta-analysis by Wang et al (27).…”
Section: Discussionmentioning
confidence: 94%